2013
DOI: 10.1186/1478-811x-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of dopamine metabolism

Abstract: Parkinson’s disease (PD) coincides with a dramatic loss of dopaminergic neurons within the substantia nigra. A key player in the loss of dopaminergic neurons is oxidative stress. Dopamine (DA) metabolism itself is strongly linked to oxidative stress as its degradation generates reactive oxygen species (ROS) and DA oxidation can lead to endogenous neurotoxins whereas some DA derivatives show antioxidative effects. Therefore, DA metabolism is of special importance for neuronal redox-homeostasis and viability.In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
430
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 534 publications
(450 citation statements)
references
References 220 publications
(264 reference statements)
9
430
1
10
Order By: Relevance
“…While O&NS can influence levels of these neurotransmitters, these neurotransmitters have antioxidative and free radical scavenging properties (Yen and Hsieh 1997). Dopamine can also be easily oxidised into the metabolite dopamine quinone, which is highly reactive and can contribute to oxidative stress (Meiser et al 2013;Miyazaki and Asanuma 2008).…”
Section: How Oandns and Inflammation Might Influence Biological Pathwaymentioning
confidence: 99%
“…While O&NS can influence levels of these neurotransmitters, these neurotransmitters have antioxidative and free radical scavenging properties (Yen and Hsieh 1997). Dopamine can also be easily oxidised into the metabolite dopamine quinone, which is highly reactive and can contribute to oxidative stress (Meiser et al 2013;Miyazaki and Asanuma 2008).…”
Section: How Oandns and Inflammation Might Influence Biological Pathwaymentioning
confidence: 99%
“…With oxygen as the electron acceptor, these reactions generate ROS, such as O 2 ¡ , and radical semiquinones and quinones during metabolism into the pigment. 1,9,11,12,18,19 Some research has shown that the toxicity of dopamine, in both animal and plant cells, is related to the synthesis of melanin and it is ROS dependent. 20,21 Overall, ROS can attack cellular components, denaturing and inhibiting proteins, causing damage to DNA and membranes, blocking the absorption of nutrients and preventing root growth.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation reactions and associated one-carbon metabolism are important for many anabolic processes as well as for detoxification of many xenobiotics and inactivation of endogenous substances such as catecholamines [42]. The methyl groups are derived directly or indirectly from methyltetrahydrofolate.…”
Section: Tracing Functional Groupsmentioning
confidence: 99%